Etnobotani Tumbuhan dalam Upacara Pernikahan dan Mengayunkan Anak pada Masyarakat Melayu di Kecamatan Kualuh Leidong, Sumatera Utara - Yayuk Asmiah; Jamilah Nasution; Abdul Karim; Riyanto Riyanto (Universitas Medan Area, 2026)
The Malay community utilizes various plant species in traditional ceremonies as part of cultural heritage passed down through generations. This study aimed to identify the plant species, plant parts used, and their cultural significance in wedding and child cradle ceremonies among the Malay community in Kualuh Leidong District, North Sumatra, Indonesia. A descriptive qualitative method was employed through observation, interviews, and documentation, with informants selected using purposive sampling. The study recorded 36 plant species belonging to 19 families used in both ceremonies. Fruits were the most frequently utilized plant parts (39%), followed by seeds (18%), leaves (15%), rhizomes (12%), tubers (9%), and stems and flowers (6% each). Plants were used as food ingredients, cooking spices, and ritual materials, particularly in the tepung tawar ceremony. Common ceremonial dishes included sweet rice, yellow rice (bale-bale), preserved sweets, nasi ulam, rendang, semur, pickles, and fermented soybean paste (tauco). Beyond their practical functions, these plants also hold symbolic meanings related to blessings, gratitude, hopes, and the cultural identity of the Malay community.